Analisis Kompensasi dan Lingkungan Kerja dalam Meningkatkan Loyalitas di PT. Citra Nusantara Catering - Nuroh, Siti; Rismayadi, Budi; Pertiwi, Wike (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research aims to analyze the role of compensation and work environment in increasing employee loyalty at PT. Citra Nusantara Catering. Qualitative descriptive methods with triangulation interviews and observation techniques were used to explore compensation conditions, work environment, and employee loyalty levels. The results of the research showed that the compensation provided by the company was below standard, with employee salary data indicating the need for adjustments to achieve higher compensation levels. adequate. The work environment also requires improvement, as indicated by workplace layout data. It is recommended to improve lighting, air circulation and layout arrangements to improve employee welfare and productivity. Employee attendance data is an additional factor that needs to be taken into account when analyzing loyalty levels. Research shows a correlation between compensation conditions, work environment, and employee absenteeism levels. With the results of this research, recommendations for reviewing compensation policies include salary adjustments, increasing incentives, and providing more comprehensive benefits. On the work environment side, improvements to lighting, air circulation and workplace layout are proposed to improve employee welfare and productivity. By implementing these steps, it is hoped that the company can increase employee loyalty, having a positive impact on overall company performance.